Analisis Kualitas Layanan Bank Syariah Indonesia Menggunakan Importance Performance Analysis - Lintang Nur Agia; Hafidzah Nurjannah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Currently, banking is experiencing rapid development so that bank management must be able to manage its business properly, this also applies to Indonesian Islamic Banks which have fewer customers than conventional banks. For this reason, Islamic banking must improve and improve the service facilities provided on an ongoing basis so that customer satisfaction is higher. The research method is a quantitative research using the Banking Service Quality (BSQ) approach and using a matrix diagram to determine which dimensions are priorities for improvement. The population in this study were all customers of Bank Syariah Indonesia in Pekanbaru City and the number of samples was 200 respondents using Roscoe technique. Keywords : Importance Performance analysis, Bank Service, Syariah Bank.